Droga dążenia do świętości według Klemensa Rzymskiego - Norbert Widok (Vox Patrum, 2012)
The third successor of St. Peter on the see of the Roman ecclesiastic community, Clement of Rome, is the author of a letter addressed to the believers in Corinth. The content of this letter offers an essential witness concerning the problems in the initial stage of the history of the Church, especially in relation to its small particle in Corinth. One of the issues discussed by Clement is encouragement for the effort of inner perfection, i.e. holiness. His offer directed to the Corinthian community contains several stages which a Christian should undergo. The ascent to holiness, according to the Bishop of Rome, starts with acknowledgement of one’s guilts. This is a condition and basis for the next stage, i.e. penance and conversion. The final stage is built on the theological virtues of faith and hope. The concept of achieving holiness, offered by Clement of Rome, is close to other witnesses of that epoch: Didache and the letters of Ignatius of Antioch.